Istikhdām Uslūb al-Taʿallum al-Taʿāwunī fī al-Tadrīb ʿalā al-Qirāʾah al-Mukaththafah - Agung Nurcholis (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
In recent years, educators have increasingly emphasized learner-centered activities that actively engage students in the teaching and learning process. Modern instructional strategies encourage students to seek knowledge independently or collaboratively with their peers, enabling them to retain information more effectively beyond the classroom. Consequently, students' roles have shifted from passive recipients of information to active knowledge seekers, while teachers serve as facilitators and guides who direct students to reliable learning resources. Among these strategies, cooperative learning has been widely recognized for its positive impact on students’ academic achievement, as demonstrated by numerous educational studies. This article discusses the implementation of the cooperative learning approach in intensive reading instruction, examines the role of the teacher in facilitating this process, and evaluates the effectiveness of this method in developing students’ intensive reading skills through selected reading texts.